Internal Fixation And Bone Grafting Of Non-Union Humeral Diaphyseal Fracture - Al-assadi, Tarik k. (AL-Kindy College Medical Journal, 2013)
Background: Humeral diaphyseal fracture usuallyheals with closed methods but when nonuniondevelops then it needs surgical intervention in theform of plating and bone grafting, intramedularynailing (open or closed simple or interlocking nails)and external fixators (circular or one plane fixator).In our unit we treated non union humeraldiaphyseal fracture with plating and bone graftingshortening of fracture ends up to 4 to 5cm whenneeded. Methods: This study was conducted atOrthopaedic Department of AL-Sadar GeneralHospital from January 2004 till December2005 .We included 20 cases with atrophic non-union in12(60%) and hypertrophic non-union in 8 (40%)patients. All atrophic non-union were treated withplating, bone shortening by transverse osteotomyand bone grafting, while hypertrophic non-unionwere treated with decortications of non-union endsand fixation with compression plates, with bonegrafting in old age. Follow up measures were basedon clinical (range of joints motion) and radiological(healing) findings. Follow up was done for upto 6months . Results: Out of 20 patients the age rangewas 20- 60 years, 16 (80%)were male and 4(20%)female. Right humerus involved in 15( 75 %)while left humerus in 5( 25%) patients.In12(60%) patients with atrophic non union boneshortening by transverse cut osteotomy was donewhile in remaining patients with hypertrophic nonunionplating was done in 2( 10 %) cases andplating with bone grafting in 6( 30%) patients.Union was achieved in all patients after 16 to 20weeks of surgery. In one patient ( 5 %) of 75 yearsage with hypertrophic non-union implant wasloosened after 3 months of surgery. At that timehealing (Union) was evident on X-rays and humeralbrace was applied for further 3 months. Twopatients( 10 %) got neuropraxia of radial nervewhich resolved with in 3 months time. 2 patients(10 %) developed shoulder stiffness which resolvedafter exercise. Conclusion: In Non Union ofHumerus shortening by transverse osteotomy &rigid fixation with plates give excellent results inselected cases.